Perceived Discrimination and Major Depression and Generalized Anxiety Symptoms: In Muslim American College Students - Lowe, Sarah R. (Journal of religion and health, 2019)
Prior research has found that Muslim Americans' discrimination experiences are associated with increased risk of mental health problems. However, few studies have included Muslim American college students or identified moderators of this relationship. Among a sample of Muslim American college students (N = 141), the current study found that perceived discrimination was positively associated with MD and GAD symptom severity. Having a strong Muslim American identity exacerbated the relationship between perceived discrimination and GAD symptoms. The findings support practices to reduce discrimination toward Muslim American college students and the need for outreach to students with a strong Muslim American identity.